Green Economy-based Agritourism Product Development with Vacuum Frying Technology - Alfanaar, Rokiy; Sunariyati, Siti; Febrianto, Yahya; Parametta, Vidya; Mariasa, Joice Cleriska; Yulita, Elia; Fatiqin, Awalul; Rahman, Sudarman; Arsana, Mu afa; Citrariana, Shesanthi; Suprayogi, Thathit (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to develop superior products at Cipta Rasa Agrotourism, Palangkaraya, through the application of vacuum frying technology. The focus of the activity included selecting the right fruits, namely crystal guava and papaya, based on their low moisture content and ease of processing. Making sample chips from these two fruits resulted in a crispy, low-oil product, while maintaining natural flavors and nutrients. In addition, the selection of appropriate packaging materials, using a combination of aluminum foil and OPP plastic, provides optimal protection of product quality and extends shelf life. An attractive and informative packaging design was also prepared to increase the product's competitiveness in the market. The results of this activity show that vacuum frying technology and good packaging design can increase the added value of agro-tourism products, support the concept of green economy, and have a positive impact on the welfare of farmers and environmental sustainability. This chip product has great potential to be marketed widely, both at the local and national levels.